Multilevel Analysis on the Determinants of Exclusive Breastfeeding at Gunung Anyar Community Health Center, Surabaya, Indonesia - Atika, Zummatul; Salimo, Harsono; Dewi, Yulia Lanti Retno (Journal of Maternal and Child Health, 2018)
Background: Exclusive breastfeeding is provision of breast milk for infants from 0 to 6 months of age with no additional food or drink intake. Provision of medicine, vitamin, and mineral is allowable during the period of exclusive breastfeeding. There is a lack of studies examining factors associated with exclusive breastfeeding in Surabaya using multilevel analysis. This study aimed to examine factors associated with exclusive breastfeeding in Surabaya using multilevel analysis. Subjects and Method: This was an analytic observational study with a cross sectional design. The study was carried out at Gunung Anyar community health center (puskesmas), Surabaya, East Java, Indonesia. A total of 25 puskesmas was selected by stratified random sampling, covering both accredited and non-accredited puskesmas. A total of 8 lactating mothers from each puskesmas were selected by simple random sampling. The dependent variable was exclusive breastfeeding. The independent variables were subjective norm, leisure time for breastfeeding, attitude, husband support, family support, and health personnel support. The data were collected by questionnaire and analyzed by a multilevel logistic regression. Results: Exclusive breastfeeding was positively affected by positive subjective norm (b=4.31; 95% CI= 1.63 to 6.99; p=0.002), leisure time for breastfeeding (b=3.97; 95% CI= 1.12 to 6.81; p=0.006), positive attitude (b=3.01; 95% CI= 0.57 to 5.45; p=0.016), strong husband support (b=2.39; 95% CI= 0.29 to 4.51; p=0.026), strong family support (b=2.71; 95% CI= 0.46 to 4.97; p=0.018), and strong health personnel support (b=4.13; 95% CI= 1.28 to 6.99; p=0.005). Posyandu showed strong contextual effect on exclusive breastfeeding with intra-class correlation (ICC)= 69.47%. Conclusion: Exclusive breastfeeding is positively affected by positive subjective norm, leisure time for breastfeeding, positive attitude, strong husband support, strong family support, and strong health personnel support. Keywords: exclusive breastfeeding, subjective norm, attitude, husband support, health personnel support Correspondence: